Geovisualization of spatial data for electoral constituencies and voters in Malaysia with web-GIS / Azman Mohd Yusof - Mohd Yusof, Azman (2012)
Geovisualization of spatial data (and most likely involves non-spatial data) requires web cartography, and the advancement of web mapping applications currently will enable virtual map of any imaginable mashups done over the web. SPR or Election Commission (EC) in Malaysia has not yet published any web-GIS for the public to access on electoral constituencies and voters through the Internet which is about time because publicly-made available data and information on their part has to rely on the conventional means through sale of constituencies' maps and voters' electoral rolls over the counter. This project attempts to provide another alternative of access to these data and information specifically for EC Selangor through the Internet for the public by using web mapping tools and technologies. Subject matter expert and focus group interviews are used to gather requirements for the web-GIS application. Electoral spatial data modeling then was derived from the data collection made from SPR Selangor. Construction of the electoral web-GIS application was later developed using cloud-based GIS which is Google Fusion Table and Google Maps API v3.